Learning Strategies in Second Language Learning and Teaching - Muho, Anita; Kurani, Aida (Mediterranean Journal of Social Sciences, 2011)
The aim of this paper is to provide a contemporary portrait of second language learning and teaching and to illustrate waysteachers can incorporate these ideas in their own teaching practice. It attempts to clarify some of the fuzziness by trying first of all toestablish basic terminology and going on to discuss definition and classification of language learning strategies. This article provides anoverview of language learning strategies for second language teachers. Using language learning strategies and training in the L2 class notonly encourages learners in their language learning but also helps teachers reflect on and improve their teaching. The development oflanguage learning strategy theory and how it fits into the framework of contemporary language teaching and learning for students whospeak other languages is examined, and research on language learning strategies to date is reviewed.